PENGARUH DISIPLIN BELAJAR DAN MOTIVASI INTRINSIK TERHADAP MINAT BELAJAR (STUDI KASUS PADA MAHASISWA POLITEKNIK ANIKA PALEMBANG) - Dian Septianti (Universitas Indo Global Mandiri)
This study aims to analyze the influence of learning discipline and intrinsic motivation on the interest of learning (case study on Polytechnic Anika Palembang students) The data analysis method used is qualitative and quantitative, with primary and secondary data source in the form of questionnaires, interviews and documentation. This research is all student of Polytechnic of Anika Palembang with sampling technique that is acidental sampling with specified number of samples counted 33 respondents.The result of research indicate that there is significant influence between learning discipline and intrinsic motivation to student's learning interest (case study at Polytechnic student of Anika Palembang) Simultaneously with Sig 0.000. While partially also found influence of learning discipline and intrinsic motivation with discipline learn to be variable that most influence to student learning interst.Key words : Learning discipline, intrinsic motivation, Interest in learning